Exploring university students' self-directed learning in online learning - Chen, Lin; Saharuddin, Norzihani (IGI Global, 2024)
This qualitative case study aims to understand the situation of university students' SDL and identify the factors that help university students solve the problem of SDL in online learning. It involved seven participants who were selected according to the inclusion criteria. Using thematic analysis of the interview data, the researchers found that the university students' perceptions of the problems of SDL in online learning are: traditional teaching and learning limits SDL, lack of effective monitoring and evaluation of the SDL process, insufficient awareness of SDL, insufficient effective resources for SDL, methods of teaching SDL need to be improved, and inadequate online learning platform. Besides, reforming online teaching and learning models, building a mechanism for monitoring and evaluating SDL, strengthening university students' knowledge of SDL, improving online learning resources, improving methods of teaching SDL, and creating an online favorable atmosphere for university students are solutions to help university students solve the problem of SDL in online learning.